KESANTUNAN BERBAHASA PADA MEDIA JEJARING SOSIAL FACEBOOK - Maulidi, Ahmad (BAHASANTODEA, 2015)
This research aimed to explain whether the use of language that contain of language politeness in social network (facebook). This research applied qualitative research which consists of two approaches (theorities approach and methodologies approach). The data of this research  was from written update status of the facebook user fulfill the principle. The data was got by observe  and write down every  data in data card. The data collection was analyzed by using normative method. The resulted of the research indicated that the use of language in social network (facebook) was consisted of politeness language. The form of  language politeness that was found in facebook question,thanked, thankful, hope,request, appreciation, invitation, offering, and information. They were applied in different variety. The differenciate was affected by the speaker, receiver, topic, setting, situation scene and the objective of the topic. Keywords: Lannguage Politeness, facebook.